Enhanced activity of eccentric contraction induces alterations in in vitro sarcoplasmic reticulum Ca2+ handling in rat hindlimb muscles - Satoshi Matsunaga; Keita Kanzaki; Takaaki Mishima; Jun Fukuda; Sumiko Matsunaga; Masanobu Wada (Japanese Society of Physical Fitness and Sports Medicine, 2015)
In order to investigate factors that contribute to eccentric contraction (ECC)-induced loss of tetanic force, Ca2+ uptake, Ca2+ release, and Ca2+-ATPase activity of the sarcoplasmic reticulum (SR) and sarcolemmal Na+-K+-ATPase activity were examined in rat fast-twitch skeletal muscles that underwent in situ ECC or isometric contraction (ISC) for up to 500 repetitions. The tetanic force at 60 Hz was more depressed in ECC-treated muscles than in ISC-treated muscles. SR Ca2+-ATPase activity displayed biphasic changes in response to ECC; after a temporary increase (up to 200 ECC repetitions), the activity decreased. With ECC, SR Ca2+ release rate and Na+-K+-ATPase activity decreased during the first 100 repetitions and remained almost constant thereafter. In contrast, the investigated variables (Ca2+-ATPase activity, Ca2+ release rate, and Na+-K+-ATPase activity) were unaltered in ISC-treated muscles. These results indicate that a more pronounced reduction in force output in ECC-treated muscles than in ISC-treated muscles might be attributable, at least in part, to impaired function of the SR Ca2+ release channel and/or Na+-K+-ATPase.